1989
DOI: 10.1007/bf01806526
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and 10-year breast cancer survival in Northern Alberta

Abstract: 1,121 women in northern Alberta diagnosed as having breast cancer between 1971-74 were followed for 10 years. Risk factors for breast cancer were studied with respect to their possible influence on survival by comparing survival curves, using both Logrank and Cox's regression model, and controlling for intercurrent death, stage and axillary node status. A complex interaction was found between age and menopausal status and survival rates. Premenopausal women aged 45-55 had a better survival rate than postmenopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
37
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 21 publications
9
37
1
1
Order By: Relevance
“…We have previously found that pregnancy within 2 years before a diagnosis of breast cancer was associated with reduced survival (Kroman et al, 1997). This, combined with the present observation of early first childbirth being a negative prognostic factor, could explain the finding reported by some researchers of an association between high parity and poor prognoses (Wang et al, 1985;Lees et al, 1989;Korzeniowski and Dyba, 1994). Women with high parity would be expected to have their first child early and have their last child late.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…We have previously found that pregnancy within 2 years before a diagnosis of breast cancer was associated with reduced survival (Kroman et al, 1997). This, combined with the present observation of early first childbirth being a negative prognostic factor, could explain the finding reported by some researchers of an association between high parity and poor prognoses (Wang et al, 1985;Lees et al, 1989;Korzeniowski and Dyba, 1994). Women with high parity would be expected to have their first child early and have their last child late.…”
Section: Discussionsupporting
confidence: 67%
“…Although some studies have not supported this observation (Mohle Boetani et al, 1988;Lees et al, 1989;Ewertz et al, 1991), there is accumulating evidence that does support it (Greenberg et al, 1985;Kogevinas, 1990;Schouten et al, 1997 (MacMahon et al, 1970;Ewertz et al, 1990 (Ewertz et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among younger women, current or recent OC use and use of higher dose and potency pills have been associated with modestly higher breast cancer incidence (3,4), but effects on survival are unclear (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). To date, no studies have examined pill characteristics and survival.…”
Section: Introductionmentioning
confidence: 99%